Isolation, identification, and cytotoxicity of a new isobenzofuran derivative from marine Streptomyces sp. W007 - 张宏宇 谢则平 娄婷婷 姜鹏 (Chinese journal of oceanology and limnology, 2016)
A new isobenzofuran derivative （1） was isolated from the marine Streptomyces sp. W007 and its structure was determined through extensive spectroscopic analyses, including 1D-NMR, 2D-NMR, and ESI-MS. The absolute configuration of compound 1 was determined by a combination of experimental analyses and comparison with reported data, including biogenetic reasoning, J-coupling analysis, NOESY, and 1H-1HCOSY. Compound 1 exhibited no cytotoxicity against human cells of gastric cancer BGC-823, lung cancer A549, and breast cancer MCF7.